Fighter Pilots With Nasopharyngeal Carcinoma Successfully Returning to Flight After Radiotherapy: A Case Series. Issue 3 (15th November 2019) - Chen, Shih-Ming; Lin, Kuen-Tze; Dai, Yang-Hong; Chiang, Kwo-Tsao; Lee, Shih-Yu
Abstract: For nasopharyngeal carcinoma (NPC), radiotherapy is the primary treatment. However, complications occur after radiation to the nasopharynx, which could potentially affect the flying safety. Four fighter pilots with NPC were reported. With early to locally advanced NPC, they received radiotherapy with or without concurrent chemotherapy. The prescribed radiation dose was 70 Gy to the primary tumor over the nasopharynx. Before treatment, all patients presented with various degrees of hearing loss on pure tone audiometry (main frequencies of 20–45 dB at 3–4.5 kHz for affected ears). After the full course of radiotherapy, tumor regression was noticed during months to years of follow-ups. The follow-up audiometry evaluation showed gradually recovered hearing function (average improvement of 5 dB at pretreatment frequencies) in all pilots. They then returned back to the flight line on annual waiver points. Here, we conclude that fighter pilots with NPC could successfully return to the flight line after radiotherapy. However, detailed physical examinations and confirmation of adaptation to flying condition are warranted.